2020
DOI: 10.1002/emp2.12253
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of emergency department resource requirements during triage: An application of current natural language processing techniques

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). Nicholas W. Sterling and Felix Brann should be considered joint first author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…Three studies compared the accuracy of triage scores assigned by multimodal models incorporating NLP to triage scores assigned by nurses. 17,36,47 Such models were more accurate than nurses in two out of three papers. 36,47 The addition of text data compared to structured data alone improved performance in assigning triage score.…”
Section: Prediction Of Triage Scorementioning
confidence: 90%
See 4 more Smart Citations
“…Three studies compared the accuracy of triage scores assigned by multimodal models incorporating NLP to triage scores assigned by nurses. 17,36,47 Such models were more accurate than nurses in two out of three papers. 36,47 The addition of text data compared to structured data alone improved performance in assigning triage score.…”
Section: Prediction Of Triage Scorementioning
confidence: 90%
“…This free-text may be more expressive, nuanced, and contain a higher level of information than structured data. 17 Prior work has suggested that incorporating free-text may improve the performance of ML at ED triage and is an important area for future research despite the challenges of incorporating free-text data into models. [18][19][20] Natural language processing (NLP) uses computational methods to analyse and understand human language and its structure.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
See 3 more Smart Citations